Aquopts: A multisource processing system for multidimensional bio-optical data integration and correction - Coelho do Carmo, Alisson Fernando [UNESP]; Shimabukuro, Milton Hirokazu [UNESP]; Imai, Nilton Nobuhiro [UNESP]; Ribeiro Bernardo, Nariane Marselhe [UNESP]; Yoshino Watanabe, Fernanda Sayuri [UNESP]; Herênio de Alcântara, Enner [UNESP] (Elsevier, 2020)
Field surveys are an important source of data for several scientific studies. Hydrological optics investigations require a large amount of optical data acquired using sensors from distinct manufacturers built with specific technologies. Consequently, rapid and integrated processing can be difficult due to several challenges, such as non-standard outputs, multidimensional resolutions of data (spatial, temporal, and spectral), mismatched sampling, sensor-specific corrections, and manufacturer proprietary software. In this context, we propose a procedure to overcome the drawbacks of processing multisource and multidimensional datasets. Our main goal is to provide a platform that integrates and analyzes datasets acquired from five sensors commonly used by the hydrological optics community. We can summarize the contribution of this work with three resources: a management model for datasets from field surveys, a processing workflow that describes all the correction steps by grouping protocols to integrate data, and an online system, Aquopts, which is a resources for storage, integration, correction, processing, and analysis. Aquopts has provided resources that have been used in several published studies in recognized geoscience journals supported by our rapid delivering system and integrated dataset processing.
Keywords: Bio-optical properties; Multidimensional representation; Multisource data; Quality control; Sensors data integration